ANALISIS PERILAKU CATCALLING SISWA DAN PENANGANANNYA (STUDI KASUS DI SMK NEGERI 10 MAKASSAR) - A. Putri Maharani Lestari; Akhmad Harum; Zulfikri; Qawiyyan Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Catcalling is a form of verbal sexual harassment that frequently occurs among adolescents and causes discomfort to its victims. This phenomenon was identified among students at SMK Negeri 10 Makassar. This study aimed to: (1) describe the forms of catcalling behavior, (2) identify the factors influencing such behavior, and (3) examine the implementation of the behavioral contract technique in reducing catcalling behavior. This study employed a qualitative approach using a case study design. The data sources consisted of the main participant, an eleventh-grade student identified by the initials MFA, and supporting informants, including the school counselor, homeroom teacher, peer, and parent. Data were collected through interviews, observations, and documentation and were analyzed using thematic analysis. The findings revealed that catcalling behavior was manifested through whistling, comments on physical appearance, and teasing verbal remarks directed at female students. The contributing factors included misconceptions about joking behavior, low self-control, peer influence, social media exposure, and insufficient parental guidance. The implementation of the behavioral contract technique involved establishing a behavioral agreement, providing positive reinforcement, and conducting continuous monitoring, which resulted in a reduction in catcalling behavior as well as improvements in students' self-awareness and control over their verbal behavior. Therefore, the behavioral contract technique can help reduce catcalling behavior in the school environment.